Wideangle seismic imaging of two modes of crustal accretion in mature Atlantic Ocean crust - Davy,R; Collier,JS; Henstock,TJ; the,VoiLA consortium (Journal of Geophysical Research: Solid Earth, 2020)
We present a highresolution 2D Pwave velocity model from a 225 km long active seismic profile, collected over ~6075 Ma central Atlantic crust. The profile crosses five ridge segments separated by a transform and three nontransform offsets. All ridge discontinuities share similar primary characteristics, independent of the offset. We identify two types of crustal segment. The first displays a classic twolayer velocity structure with a high gradient layer 2 (~0.9 s1) above a lower gradient layer 3 (0.2 s1). Here PmP coincides with the 7.5 km s1 contour and velocity increases to >7.8 km s1 within 1 km below. We interpret these segments as magmaticallyrobust, with PmP representing a petrological boundary between crust and mantle. The second has a reduced contrast in velocity gradient between upper and lower crust, and PmP shallower than the 7.5 km s1 contour. We interpret these segments as tectonically dominated, with PmP representing a serpentinized (alteration) front. Whilst velocity depth profiles fit within previous envelopes for slowspreading crust, our results suggest that such generalizations give a misleading impression of uniformity. We estimate that the two crustal styles are present in equal proportions on the floor of the Atlantic. Within two tectonically dominated segments we make the first wideangle seismic identifications of buried oceanic core complexes in mature (> 20 Ma) Atlantic Ocean crust. They have a ~20 km wide “domal” morphology with shallow basement and increased uppercrustal velocities. We interpret their midcrustal seismic velocity inversions as alteration and rocktype assemblage contrasts across crustalscale detachment faults.